Legal boundaries and conservation: The case of Seasonally Dry Forests of the Serra da Bodoquena National Park, Brazil - Damasceno Junior, Geraldo A.; Oliveira, Maxwell R.; Alves, Flávio M.; Silva, Rosa Helena da; Pott, Vali J.; Spielmann, Adriano A.; Aptroot, André; Pereira, Sandro R. S.; Batista, Suziele G.; Silva, Lucas E. da; Nakamura, Vivian A.; Pott, Arnildo (Acta Botânica Brasílica, 2024)
ABSTRACT The Serra da Bodoquena National Park is an important protected area that promotes the conservation of a threatened ecosystem, the Dry Forest. It comprises two major fragments of predominantly Seasonally Dry Forest vegetation. The two fragments are under different protection schemes because they are considered different biomes. The southern fragment is considered part of the Atlantic Forest biome, and is thus protected by the Atlantic Forest Law, while the northern one is considered part of the Cerrado biome and is protected by the Native Vegetation Protection Law of Brazil (2012). This difference affects management and threatens the conservation of the National Park. The Native Vegetation Protection Law is more permissive, thus increasing the conflicts between the park and surroundings in the northern fragment. We used floristic composition to provide a more accurate definition for the two fragments with regard to their phytogeographical domain. Our results identified high floristic similarity between the fragments, indicating the same vegetation type for both. Among the 202 plant species identified in this study, 76% belong to the Atlantic Forest biome. This relatively high proportion indicates that the predominant vegetation and species composition of the National Park is typical of the Atlantic Forest. The occurrence of fragments of the Atlantic Forest, with a representative number of species of its flora outside the area of application of the law of the Atlantic Forest, defined by Decree No. 6.660 / 2008, indicates the need to elaborate or adapt the law to protect these fragments.